Case Report: Difficult radial artery sheath removal: a report of two cases and review of the literature - Yang, Bangguo; Yeh, Mengqi; Bai, Jie (Frontiers in Cardiovascular Medicine, 2025)
The transradial approach to coronary angiography and interventional therapy has gained worldwide popularity in recent years due to its lower rate of vascular complications compared to the femoral approach. We present two cases of patients who experienced difficulties in removing the radial artery sheath. In the first case, the sheath inadvertently fractured within the radial artery, but it was successfully extracted using hemostatic forceps. In the second case, a severe spasm of the radial artery complicated sheath removal, resulting in the sheath becoming stretched and deformed. Ultimately, the deformed sheath was removed slowly and successfully with the assistance of a guidewire and catheter. Furthermore, we conducted a review of existing literature to delineate management strategies for situations where sheath removal poses challenges.